Analysis of Village Fund Financial Ratios in Implementing Development Programs in Mata Allo Village, Bontomarannu District, Gowa Regency - Nurafni, Nurafni; Muchriana Muchran; Nasrullah, Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to find out how the financial ratio of village funds is in implementing development programs in Mata Allo village, Bontomarannu sub-district, Gowa district. This research uses descriptive quantitative analysis. By focusing on financial ratios of funds in implementing development programs. The types and sources of data used are primary data and secondary data obtained from observation, documentation and financial reports. The results of this research show that the activity ratio of Mata Allo Village has decreased every year from the 2021 to 2023 fiscal year. Because the activity ratio prioritizes larger village funds in routine operational expenditure, this results in a reduction in the share of capital expenditure so that funds from routine operational expenditure will be earmarked for providing facilities and infrastructure for the local community as village investment. The effectiveness ratio of Mata Allo Village can be categorized using effective criteria. This is shown by the average realization of revenue for 2021-2023 of 99.97%, which means that almost 100% of the targets to be achieved will be achieved. The efficiency ratio of the Mata Allo Village government is categorized as inefficient because the average amount obtained each year is 100 .13% of the achievements obtained indicate that the performance of the village government in managing PAD is inefficient as indicated by the results of the ratio calculation being above 100%. Allo Village Funds can be seen from the financial ratio of village funds which decreases every year.